Postać Piotra w Ewangelii św. Mateusza - Paciorek, Antoni (Vox Patrum, 2004)
The author of this work tries to answer the question: „what picture of St. Peter is showed by the first Gospel?". It appears that the figure of St. Peter is not changed meaningly in texts taking over from Mark’s version (4,18; 8 ,14nn; 6, 18; 16, 23; 17, 1-8; 26, 33; 26, 69-75) by Matthew. Meaning of describing events is the same in both cases though a little changes emphasizes the role of Apostles’ Prince. In the other hand, missing by Matthew Mark’s texts about Peter (Mk 1, 36; 5, 37; 13, 3; 16, 7) is not the trial of decreasing the role of St. Peter. There are three novelty Matthew’s texts in view of St. Peter’s person. These texts don’t run parallel to synoptics’ words. There are: going to Jesus on the water (14, 28-31), confession somewhere Caesarea Philippi way (16, 16-19) and the matter of temple taxes (17, 24-27). The most suggestive is the person of St. Peter in the fundamental! texts for Matthew Mt 16, 17-19. It is obvious that meaning and priority of St. Peter comes down from earth activity of Jesus.